Quality of life and physical activity participation in adolescent girls with idiopathic scoliosis treated with bracing - Ellysa Okky Gusma; Gatot Sunarto; Gian Lisuari Adityasiwi; Nathan Agwin Khenda; Nicolas Adi Perdana Susanto (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Adolescent idiopathic scoliosis (AIS) is a common musculoskeletal condition that predominantly affects adolescent girls and often requires prolonged brace treatment. Although bracing is effective in preventing curve progression, it may negatively influence physical comfort, emotional well-being, and psychosocial functioning. Quality of life has therefore become an essential outcome in the management of AIS. Physical activity, particularly swimming, is frequently recommended as a safe form of exercise for adolescents with scoliosis; however, evidence on its association with quality of life during brace treatment remains limited. Research Methodology: This study employed a quantitative cross-sectional design involving 50 adolescent girls aged 10–18 years diagnosed with idiopathic scoliosis and undergoing brace treatment for at least six months. Participants were selected using purposive sampling. Quality of life was assessed using the Brace Questionnaire (BrQ), covering eight domains. Physical activity participation was measured by swimming frequency and categorised as low (1–2 times/week) or high (≥3 times/week). Data were analysed using univariate statistics, independent t-tests, and multivariate regression analysis. Results: The mean total quality-of-life score indicated a moderate level of quality of life among participants. Higher participation in physical activity was significantly associated with better physical and emotional functioning, vitality, and overall quality of life (p < 0.05). Adolescents who swam three or more times per week had higher total quality-of-life scores than those who swam fewer times per week. No significant differences were observed in self-esteem and social functioning domains. Conclusion: Regular physical activity, particularly swimming, is positively associated with improved quality of life among adolescent girls with idiopathic scoliosis undergoing brace treatment. Integrating safe physical activity promotion into conservative scoliosis management may enhance both physical and psychosocial well-being.